KEPEMIMPINAN JAWA TOKOH UTAMA DALAM NOVEL KEN AROK KEN DEDES: SEBUAH ROMAN EPIK CINTA PENUH DARAH KARYA WAWAN SUSETYA DAN TOKOH UTAMA DALAM LEGENDA "GUNUNG KEMUKUS DI SRAGEN": KAJIAN SASTRA BANDINGAN DAN IMPLEMENTASINYA SEBAGAI BAHAN AJAR SASTRA DI SMK BINA TARUNA MASARAN - WIDYASTUTI, INTAN PANDINI, Dr. H. Nafron Hasjim (2016)
ABSTRACT Intan Pandini Widyastuti/A310120261. MAIN CHARACTER'S JAVANSSE LEADERSHIP IN KEN AROK KEN DEDES: SEBUAH ROMAN EPIK CINTA PENUH DARAHNOVEL BY WAWAN SUSETYA ANF MAIN CHARACTER IN "GUNUNG KEMUKUS IN SRAGEN" MYTH: LITERATURE EQUIVALENT REVIEW AND THE IMPLEMENTATION AS LITERATURE LEARNING MATERIAL IN SMK BINA TARUNA MASARAN. Skripsi. Indonesia Language Education, Teacher Training and Education, Muhammadiyah University of Surakarta. October, 2016. This research aims to (1) describe the structur which builds Ken Arok Ken Dedes: Sebuah Roman Epik Cinta Penuh Darahnovel by Wawan Susetya and "Gunung Kemukus" in Sragen myth", (2) review the similariry and the differences of ken arok's javanesse leadership in Ken Arok Ken Dedes: Sebuah Roman Epik Cinta Penuh Darahnovel by Wawan Susetya with Prince Samoedra in "Gunung Kemukus" in Sragen myth", (3) analyze the research outcome implementation of Ken Arok Ken Dedes: Sebuah Roman Epik Cinta Penuh Darah novel by Wawan Susetya with Prince Samoedra in "Gunung Kemukus" in Sragen myth" as litarature learning material in SMK Bina Taruna. This research use descriptive qualitatif method. The data collecting technique in this research are documentation, observation, and interview.the data velidity use triangulation of the data. Data analysis technique use equivalent litarature analysis. Based on the research, it can be conclude that (1) the stucture which build Ken Arok Ken Dedes: Sebuah Roman Epik Cinta Penuh Darahnovel and myth of "Gunung Kemukus" are theme, character, plot, bacground. (2) the similarity and the differences of javanesse leadership in Ken Arok Ken Dedes: Sebuah Roman Epik Cinta Penuh Darahnovel and the myth of "Gunung Kemukus" is the characteristic of the leadership they are monocentrum, metafysis and sincretis, on the leadership value i.e. jujur, wani dan temen. (3) the result of this research can be implemnted on literature learning in XI grades of senior high school based on KD 7.2 to analyze instrinsic and extrinsic unures of Indonesian novel/translated novel. Beside that, in literature learning in X grades of senior high school based on KD 13.1 to find an interesting things about the characters directly or through recording. Keyword : equivalent literature, javanesse leadership, Ken Arok Ken Dedesnovel, Gunung Kemukus